ANALISIS FAKTOR YANG MEMPENGARUHI KEJADIAN MASTITIS SUBKLINIS DAN KLINIS PADA SAPI PERAH (STUDI KASUS DI KOPERASI AGRIBISNIS DANA MULYA KECAMATAN PACET, KABUPATEN MOJOKERTO) - Nisa, Hefi Choirun; Purnomo S., Bambang; Damayanti L., Tita; Hariadi, Mas'ud; Sidik, Romziah; Harijani, Nenny (Ovozoa: Journal of Animal Reproduction, 2019)
The study was conducted to know the factor that potentially affect the incidence of subclinical and clinical mastitis in dairy cows in the area Agribusiness Cooperative Dana Mulya Pacet, Mojokerto. Data retrieval were done by examining the incidence of subclinical and clinical mastitis in 100 lactation dairy cows. Milk samples were taken from milking each quarter of dairy cows in the afternoon, then tested using CMT reagent (California Mastitis Test). In addition data was obtained from farmers through structured questionnaires. The data was processed and presented in tabular form and analyzed statistically by the method of regression trees. The conclusion of this research showed that dairy cows in the area of Agribusiness Cooperative Dana Mulya Pacet, Mojokerto affected by subclinical mastitis reached 76% and clinical mastitis 11%. This was influenced by the milking sequence factor of the nipple which was not distinguish between sick and healthy nipples, the lack of sanitation before milking, and the location of livestock disposal is too close to the cowshed.